Flights of fantasy: A reformulation of the flyers' dilemma. (September 2015) - Young, Martin; Markham, Francis; Reis, Arianne C.; Higham, James E.S.
Highlights: Flying anxiety and climate change are dialectically-related symptoms of the risk society. Risk-free flying via commodity fetishism is not yet technologically feasible. Alternative futures are themselves science-fiction-based cultural productions. We are unable to imagine emancipatory futures due to our ideological subjectification. We are obliged to attempt a philosophical resolution to this 'dilemma of ahistoricity'. Abstract: We position pleasure travel within Beck's risk society as a contradictory form of consumption that simultaneously produces individual pleasure and global environmental risk. We examine the paradoxical emergence of the 'anxious traveler' from this contradiction, arguing that this social category is necessary to individualize and apportion the global, environmental risk associated with frequent flying, and hence legitimate the reproduction of unsustainable travel practices. We identify several future scenarios that may synthesize this frequent-flying dialectic. On reflection, these scenarios themselves appear as cultural productions, suggesting that our attempts to imagine the future are crippled by the hegemonic ahistoricism associated with contemporary capitalism.